Tc-99m hydroxymethylene diphosphonate SPECT/CT for the evaluation of osteonecrosis of the jaw: preliminary study on diagnostic ability of maximum standardised uptake value. Issue 1 (January 2020) - Ogura, I.; Sasaki, Y.; Sue, M.; Oda, T.; Kameta, A.; Hayama, K.
Abstract : AIM: To investigate the diagnostic ability of maximum standardised uptake value (SUVmax ) at combined single-photon-emission computed tomography/computed tomography (SPECT/CT) for the evaluation of osteonecrosis of the jaw. MATERIALS AND METHODS: Seven patients with mandibular osteonecrosis (three osteoradionecrosis, three medication-related osteonecrosis of the jaw (MRONJ), and one rheumatoid arthritis) underwent SPECT/CT at 4 hours after injection of technetium 99m hydroxymethylene diphosphonate. The SPECT/CT parameters SUVmax were compared for the osteonecrosis with normal mandible. Statistical analyses among the SUVmax of osteonecrosis were performed by one-way repeated measures analysis of variance with Tukey's HSD (honestly significant difference) test. A p- value <0.05 was considered statistically significant. RESULTS: SUVmax for MRONJ and rheumatoid arthritis (23.24±8.63) were significantly higher than those for osteoradionecrosis (9.05±1.39, p= 0.005) and normal mandible (3.57±0.46, p= 0.000). CONCLUSIONS: SUVmax derived from bone SPECT/CT could be useful for the evaluation of osteonecrosis of the jaw. Highlights: SUVmean of SPECT/CT for normal mandible were lower than those for osteonecrosis. SUVmax for MRONJ were significantly higher than those for osteoradionecrosis. SUVmax may be useful for the evaluation of osteonecrosis of the jaw.